Visible-Light-Induced Decarboxylative Functionalization of Carboxylic Acids and Their Derivatives - Xuan, Jun; Zhang, Zhao-Guo; Xiao, Wen-Jing (Angewandte Chemie International Edition, 2015)
Visible‐light‐induced radical decarboxylative functionalization of carboxylic acids and their derivatives has recently received considerable attention as a novel and efficient method to create CC and CX bonds. Generally, this visible‐light‐promoted decarboxylation process can smoothly occur under mild reaction conditions with a broad range of substrates and an excellent functional‐group tolerance. The radical species formed from the decarboxylation step can participate in not only single photocatalytic transformations, but also dual‐catalytic cross‐coupling reactions by combining photoredox catalysis with other catalytic processes. Recent advances in this research area are discussed herein. Photo op: A novel functionalization reaction using visible‐light‐induced photoredox catalysis has recently been developed (see title). The formed radical species can participate in not only single photocatalytic transformations, but also dual‐catalytic reactions by combining photoredox catalysis with other catalytic methods. Recent advances in this research area are discussed herein.